The Interaction of Contact Product and Factor IX - Cattan, A. D; Denson, K. W. E (Thrombosis and Haemostasis, 1964)
1. The activation of factor IX in recalcified plasma develops slowly and is accelerated by dilution of the resulting serum.2. The complex process of activation and decay of the active product, introduces error into the assay method.3. An excess or the complete removal of calcium ions eliminates the activation but does not prevent decay of the active product.4. The assay of factor IX in plasma gives results similar to those for serum obtained from celite exhausted plasma.5. Activation of factor IX is minimal in the serum obtained when plasma samples deficient in contact product, or the contact factors are clotted.6. Plasma factor IX is probably activated enzymatically by calcium ions and contact product. The presence in serum of an inhibitor of the process was not clearly demonstrated.